ZERDÜŞTÎLİK ve YEZİDİLİK BAĞLAMINDA KÜRTLERİN İNANÇLARININ KÖKENİ PROBLEMİ - Sular, Mehmet Emin (My University, 2020)
M. Ö. 2000’li yıllardan itibaren Sümer ve Asur kaynakları Kürt ismine yakın halkların varlığını haber vermektedir. Kökenleri Ârilere dayanan Kürtler, İslam’ı kabule kadar ataları Ârilerden aldıkları geleneksel inançlarına bağlı kalmışlardır. Buna rağmen 20. yüzyılın başından itibaren bir kısım milliyetçi Kürt aydını, Medlerin (M.Ö. 728-550) Kürtlerin atası, Zerdüşt’ün Med/Kürt, İslam’dan önce Kürtlerin Zerdüştî olduğunu,Kürtlerin İslam öncesi dini olarak idealize edilen Yezidiliğin Zerdüştîliğe dayandığınıiddia etmiştir. Kürt milliyetçiliğine bağlı olarak gelişen bu iddiaların merkezinde,oluşturulmak istenen yeni Kürt ulus kimliği için şanlı bir tarih ve kadîm din yaratmakvardır. Söz konusu iddiaların ispatı için bazı yazılı ve arkeolojik deliller ileri sürülmüştür. Bu düşünce zamanla toplumun okur-yazar belli kesimi tarafından da kabul görmüştür. Çalışmada söz konusu iddialar ele alınmış ve ileri sürülen delillerincelenmiştir. Bu bağlamda Zerdüştîliğin daha çok Perslere/Farslara ait bir din olduğu,Medlerin Kürtlerin atası olmadığı, Zerdüşt’ün de Med döneminde yaşamadığı, Kürtlerin İslam’ı kabule kadar Ârilerden getirdikleri politeist ve tabiat olaylarını kutsal gören geleneksel inançlarına bağlı kaldıkları sonucuna ulaşılmıştır. İslam öncesi Kürt inançlarının bir manzumesi niteliğinde olan Yezidiliğin de Zerdüştîliğe dayandığına dair iddiaların temellendirmeden yoksun olduğu anlaşılmıştır.Konuyla ilgili Kuzey Irak’ta alan araştırması yapılmış ayrıca Türkçe, İngilizce, Arapça yazılı kaynaklardan ve görsel materyallerden faydalanılmıştır.

Since the 2000s BC, Sumerian and Assyrian sources have been reporting the presence of publics close to the Kurdish name. The Kurds, whose roots are based on Arites, have adhered to their traditional beliefs that they took the ancestors from the Aris until Islam accepted. Nevertheless, since the beginning of the 20th century, some nationalist Kurdish intellectuals claimed that Medes (728-550 BC) were the ancestors of the Kurds, so Zoroaster was Med/Kurd, before the Islam the Kurds were Zoroastrian and that syncretic belief, Yazidism, was based on Zoroastrianism. At the center of these claims, which are based on nationalism, is to create a glorious history and an ancient religion for the new Kurdish nation identity desired to be created. Some written and archaeological evidence has been proposed to prove the allegations in question. Over time, this idea has been accepted by certain sections of the society who are literate. Therefore, in our study, the allegations in question were handled and the evidences put forward were examined. As a result, it was observed that Zoroastrianism was mostly a Persian religion, Kurds and Medes were different branches of the Aris, that Zoroaster did not live during the Medes period and that the Kurds adhered to their traditional beliefs, which considered the politeist and natural events sacrificed by the Aris until the acceptance of Islam. It was understood that Yazidism, which is a poem of pre-Islamic Kurdish beliefs has been understood that the claims that Yazidism is also based on Zoroastrianism insubstantial. In addition, field research was conducted in Northern Iraq on this subject, and besides, Turkish, English and Arabic written sources and visual materials were used.
THE ORIGIN PROBLEM OF KURDISH BELIEFS IN THE CONTEXT OF ZOROASTRIANISM AND YAZIDISM